2020
DOI: 10.31234/osf.io/e2kr7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Test-retest reliability of four cognitive tasks in a not so WEIRD sample

Abstract: Most cognitive tasks have been designed and tested in samples from Western, Educated, Industrialised, Rich, and Democratic (WEIRD) countries and it is usually assumed that their psychometric properties remain consistent regardless of culture. However, several studies have observed that culture can have important effects on cognition, which may ultimately affect the reliability of these tasks. In the present study, test-retest reliability of the Colour Word Stroop Task, Sustained Attention to Response Task, Sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 60 publications
(76 reference statements)
1
5
0
2
Order By: Relevance
“…Switching between dual-tasks inhibits excitatory drive from the frontal eye fields and inhibit reflexive pro-saccades—essentially making an anti-saccade easier to perform and reducing the difference between pro- and anti-saccade latency 70 . For the Stroop test, part two error was consistent with previous research 71 , 72 , but our Part one error rates were lower (~ 15%) than normative data (~ 30%) 71 , 72 , but with poorer reliability (ICC = − 0.04) than reported by others 73 , 74 . Further investigation shows this to be confusion between the green and yellow colors—potentially explaining why there appeared to be a learning effect during Stroop testing—which was corrected through a more comprehensive introduction 37 .…”
Section: Discussionsupporting
confidence: 91%
“…Switching between dual-tasks inhibits excitatory drive from the frontal eye fields and inhibit reflexive pro-saccades—essentially making an anti-saccade easier to perform and reducing the difference between pro- and anti-saccade latency 70 . For the Stroop test, part two error was consistent with previous research 71 , 72 , but our Part one error rates were lower (~ 15%) than normative data (~ 30%) 71 , 72 , but with poorer reliability (ICC = − 0.04) than reported by others 73 , 74 . Further investigation shows this to be confusion between the green and yellow colors—potentially explaining why there appeared to be a learning effect during Stroop testing—which was corrected through a more comprehensive introduction 37 .…”
Section: Discussionsupporting
confidence: 91%
“…It is important to highlight that experimental psychology, in general, and cognitive psychology, in particular, are not taught at the University of Guayaquil. Students were therefore extremely naive about cognitive psychology and the instruments commonly used in the field (Rodas & Greene, 2020b). We consider the use of this population an additional strength of the study, because Ecuadorian participants do not share many of the characteristics of WEIRD populations (Henrich et al, 2010; Rodas & Greene, 2020b) and can thus provide evidence regarding the effectiveness of cognitive training in less commonly investigated samples.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to highlight that experimental psychology in general, and cognitive psychology in particular, are not taught at the University of Guayaquil. Students were therefore extremely naive about cognitive psychology and the instruments commonly used in the field (Rodas & Greene, 2020a). In this sense, the use of this sample constitutes an important contribution to the study, since it allows for an assessment less affected by the effects of test-wiseness which is very difficult to avoid in studies using samples where psychology research is far more common.…”
Section: Effects Of An N-back Training On Executive Functionsmentioning
confidence: 99%
“…In the current study, a single dimension was computed, chiefly due to the high internal consistency observed in our sample (α = 0.89). A Spanish version of the scale (Rodas and Greene, 2020) was utilised for this study, which has demonstrated good internal consistency (α = 0.8) and a satisfactory fit in factor analyses.…”
Section: General Health Questionnaire 12-item Version (Ghq-12)mentioning
confidence: 99%